GEOLOGI DAERAH PALAES DAN SEKITARNYA KECAMATAN LIKUPANG BARAT, KABUPATEN MINAHASA UTARA, SULAWESI UTARA - KADIR, ALVYUS; Budiharso, Agus Santoso; Rachmadhan, H.D. (Journal Geological Processes, Risks, and Integrated Spatial Modeling, 2025)
This research aims to analyze the geological conditions of the Palaes area and its surroundings in West Likupang District, North Minahasa Regency, North Sulawesi. The study covers an area of approximately 16 km², administratively including the villages of Palaes, Lansa, Lantung, Kulu, and Warisa. The research method involves surface geological mapping at a scale of 1:10,000, including geomorphological observation, lithological analysis, structural measurement, and petrographic analysis. Data were processed using the Dips software and spatial analysis based on DEMNAS to interpret morphological lineaments. The results show that the geomorphology of the study area consists of six landform units formed by three main genetic processes: structural, denudational, and fluvial. The stratigraphy comprises four lithological units: the Palaes Sandstone Unit, the Palaes Breccia Unit, the Lansa Andesitic Lava Unit, and the Alluvial Unit. Structural data indicate dominant lineaments trending northwest–southeast, interpreted as normal faults, evidenced by geomorphic features such as waterfalls and straight valleys. The geological history reflects a sequence of sedimentation and volcanic activity, followed by tectonic processes that shaped the major geological structures of the region. This research produced a geological map, a geomorphological map, and a stratigraphic column that serve as a scientific basis for geological resource exploration, hazard assessment, and land-use planning based on local geological characteristics.